Covariation Between Midline Cranial Base, Lateral Basicranium, and Face in Modern Humans and Chimpanzees: A 3D Geometric Morphometric Analysis. Issue 4 (5th February 2013) - Neaux, Dimitri; Guy, Franck; Gilissen, Emmanuel; Coudyzer, Walter; Ducrocq, Stéphane
<x xml:space="preserve">Abstract</x> Previous studies showed that in modern humans the basicranium is formed of two modules: the midline cranial base and the lateral basicranium which are integrated with the face in very different ways. The study of the relationship between these structures is of prime interest in the context of hominids craniofacial evolutionary history. In this study, we aim to test if the relationship between the midline cranial base and the face on one hand and the lateral basicranium and the face on the other hand are qualitatively and quantitatively different in modern humans and chimpanzees: two phylogenetically close but morphologically different hominids. This work is performed using three‐dimensional (3D) landmarks to take into account the face and basicranium 3D shape. Modern humans and chimpanzees both exhibit a significant relationship between lateral basicranium and face, and a nonsignificant relationship between midline cranial base and face. However, the patterns of integration are different for the two species. These results underscore the essential role of the lateral basicranial shape in the setting of the facial morphology in modern humans and chimpanzees. The important differences in the patterns of integration may be related to the genetic, developmental, and functional requirements of each taxon, acquired along their respective evolution. From a common, tight, relationship between lateral basicranium, and face, each taxon may develop different patterns of integration in order to adapt to particular functions and morphologies. Anat Rec, 296:568–579, 2013. © 2013 Wiley Periodicals, Inc.